3 8 + 6 4 3 7 2 3 + 5 8 5 + 3 8 + 6 4 3 7 2 3 − 5 8 5 = ?
Give your answer to 3 decimal places.
This problem is part of this set
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
wow this is great!
Elegant solution my friend
i don't have much time to do these types of math
Problem Loading...
Note Loading...
Set Loading...
⇒ 3 8 + 6 4 3 7 2 3 + 5 8 5 = 3 8 + 8 9 + 6 4 3 5 8 5 = 3 8 7 3 + 6 4 3 5 8 5
⇒ 3 8 + 6 4 3 7 2 3 − 5 8 5 = 3 8 + 8 9 − 6 4 3 5 8 5 = 3 8 7 3 − 6 4 3 5 8 5
Let A = 3 8 7 3 + 6 4 3 5 8 5 , B = 3 8 7 3 − 6 4 3 5 8 5 and S = A + B = 3 8 7 3 + 6 4 3 5 8 5 + 3 8 7 3 − 6 4 3 5 8 5
Now,
S 3 = A 3 + B 3 + 3 A B ( A + B ) = A 3 + B 3 + 3 A B S ⇒ ( ∗ )
Thus,
A 3 + B 3 = ( 3 8 7 3 + 6 4 3 5 8 5 ) 3 + ( 3 8 7 3 − 6 4 3 5 8 5 ) 3 = 4 7 3
3 A B = = 3 ( 3 8 7 3 + 6 4 3 5 8 5 ) ( 3 8 7 3 − 6 4 3 5 8 5 ) = 3 3 ( 8 7 3 ) 2 − ( 6 4 3 5 8 5 ) 2 3 3 6 4 5 3 2 9 − 4 0 9 6 1 1 4 0 7 5 = 3 3 4 0 9 6 2 2 6 9 8 1 = 3 ( 1 6 6 1 ) = 1 6 1 8 3
Instead A 3 + B 3 with 4 7 3 and 3 A B with 1 6 1 8 3 in equation ( ∗ )
S 3 = 1 6 S 3 = 1 6 S 3 − 1 8 3 S − 2 9 2 = ( S − 4 ) ( 1 6 S 2 + 6 4 S + 7 3 ) = 4 7 3 + ( 1 6 1 8 3 ) S 2 9 2 + 1 8 3 S 0 0
From equation
⇒ S − 4 = 0 ⇒ S = 4
⇒ 1 6 S 2 + 6 4 S + 7 3 = 0 ⇒ Δ = 6 4 2 − 4 ( 1 6 ) ( 7 3 ) = − 5 7 6 < 0 [Complex Solution]
Hence, 3 8 + 6 4 3 7 2 3 + 5 8 5 + 3 8 + 6 4 3 7 2 3 − 5 8 5 = 4